(untitled) (Research, Society and Development, 2021)
Refrigerated raw milk must be obtained in a hygienic manner, following strict protocols so that there is no possibility of alterations in its composition. Brazilian legislation stipulates that milk must be refrigerated at the farm within three hours after milking, at a temperature equal to or lower than 4ºC, and the alizarol stability test must be performed by the transporter before milk collection, obeying physicochemical and microbiological standards before unloading at the dairy industry. The Standardized Plate Count (SPC) analysis of milk aims to verify the hygiene of the milking and property facilities and the standard is 300x10³ CFU/mL which is acceptable, while the somatic cell count (SCC) analysis indicates the presence of mastitis in the dairy herd. This paper describes the results of the evaluation of routine milk collection routine in 30 rural properties for comparison of the temperature indicated on the expansion tank panel and the temperature measured in situ, using a saliva thermometer. Analysis of the stability of alizarol 78% v/v was also carried out, as well as the collection of 3 milk samples for CPP and CCS analysis at an external accredited laboratory. Most (66.6%) of the milk cooler temperature values found corresponded to the correct milk temperature measured (in situ) by a calibrated thermometer. In only three properties was there an inconsistency in the analysis of alizarol stability, resulting in the rejection of the milk collection. The results of the PPC analysis indicated non-compliance in 7 properties (23.3%), while the SCC indicated non-compliance in 21 properties (70.0%), with a high rate of mammary infections among the animals milked in the properties.